Identification as the Basis for a Theory of Motivation - Foote, Nelson N. (American Sociological Review, 1951)
R OLE theory has suffered since inception from lack of a satisfactory account of motivation. It is all very well as far as it goes to state that a person learns to recognize standard situations and to play expected roles in them according to the status defined for him in each. But this is not enough when the person encounters alternatives and must resolve conflicting definitions of his appropriate behavior.1 Nor is it enough to account for the emergence of new roles in his conduct, nor for his more or less unique variations upon conventional roles. A striking revelation of the need for some theory of motivation to back up situational analysis2 is disclosed by apathy in the performance of conventional roles, when these are on the verge of abandonment or are accepted only under duress. Roles as such do not provide their own motives. Most of the recent writers on role theory3 have recognized this deficiency and have endeavored to make it up through the expedient of eclecticism. Like a Ford car with a Chevrolet motor, each of these integrators puts on the road his own model of role theory, one powered by psychic energy, another by a system of tensions or a drivereduction apparatus, a third by some hierarchy of innate and derived needs. Also, a